Pathway 2 Podium : a multidisciplinary and mixed method approach to enhancing the efficacy of talent development systems - Langham-Walsh, E. (Bangor University, 2020)
This thesis expands on the current expertise development literature building upon previous research in the field (Güllich et al., 2019; Jones et al., 2019). It aims to highlight problems associated with identification in talent systems and looks to undertake multidisciplinary and prospective research to gather insight into sport specific nuances in talent development. It is the first research of its kind to longitudinally and prospectively examine all multidisciplinary factors relevant to talent development within individual sports. This thesis contains six chapters, four of which are empirical studies. Chapter 1 critically reviews the relevant literature relevant to talent identification and development (TID) specifically: the underpinnings of "talent"; the problem with talent identification; talent development models and approaches; and influential factors in athlete TID. This chapter addresses the empirical limitations of previous TID research providing rationale for this thesis. These discussions are centred around the lack of longitudinal, multidisciplinary, and prospective research that examines sports as individual entities providing us with a framework for our research. Chapter 2 explores the relative age effect in gymnastics and takes a novel approach emphasised by Jones et al. (2018) by further examining the prevalence of intra-sport differences. Poisson regression analysis indicated no relative age effect in the full sample of elite, international, women's artistic gymnasts but an effect that manifested when analysing apparatus independently. Our results identified that relatively younger gymnasts were 27% and 21% more likely to make major international beam and vault finals respectively. Our findings can be attributed to the influence of self-fulfilling prophecy (Merton, 1948) upon coach and gymnast expectations, as well as the technical mechanisms underpinning skill development involved in the underdog hypothesis (Gibbs et al., 2012). This chapter adds to the limited research base surrounding the influence of the RAE in gymnastics, whilst also being the first study to our knowledge to examine the differences of apparatus specialism. Chapter 3 presents three studies that seek to develop the Athlete Psychosocial Survey (APS), a brief profiling tool gauging athletes' scores on psycho-social factors influencing elite performance. The first two studies consisted of item generation and instrument construction, with initial analysis confirming the preliminary concurrent and convergent validity of the measure. The third study utilised a novel analytical strategy and provided evidence for the predictive validity of the APS with the ability to discriminate between two samples of high- and low- level hockey players with 87% accuracy. The practicality of our measure means that coaches and practitioners can gauge many psychosocial constructs pertinent to athlete development and readily incorporate them into their talent development programmes. This in turn aids the progression of talent development systems by enabling the integration of multiple perspectives alongside greater athlete insight for coaches and practitioners than what is currently available. Chapter 4 takes a longitudinal, prospective, and multidisciplinary approach to talent development within canoe sprint. Data was collected over a period of 18 months and analysed using state of the art machine learning analysis. Following this an 11-feature model was identified consisting of multidisciplinary variables that could discriminate between high- and low- potential athletes with 79% accuracy. Specifically, this chapter highlighted the interactive influence of an athlete's early developmental experiences, the microstructure of practice, and their ability to cope with challenge on their development. The results of this chapter were discussed with a working group of British Canoeing managers, coaches, and support staff to enhance the interpretation of the findings and provide recommendations going forward. Chapter 5 followed on from a quantitative, multidisciplinary investigation of factors relevant to the development of canoe slalom athletes and qualitatively examined the psychosocial factors and experiences that underpinned an athlete's developmental journey. Taking a critical realist approach, we built upon Hardy et al.'s (2017) findings and undertook semi-structured interviews with four pathway level athletes. Seven themes from our data emerged as influential to athlete progression specifically: (a) early developmental experiences, (b) relationship with sport, (c) personality, (d) ongoing developmental experiences, (e) athlete behaviors, (f) support networks, and (g) pressure zone and emotion regulation. Our findings add to the broader knowledge base surrounding the psychosocial processes underpinning the development of elite athletes whilst also providing important implications for applied practice. Chapter 6 is a general discussion and compiles of the main findings from this thesis. We discuss the practical and theoretical implications that emerge from this research and propose future research directions to advance this research further. Finally, Chapter 7 presents examples of the dissemination and impact work completed alongside this thesis.